A mindful product acceptance model. Issue 1 (2nd January 2018) - Ta, Anh; Prybutok, Victor
ABSTRACT: We posit, develop and test a new mindful product acceptance model that includes the independent variable constructs of perceived ease of use, perceived usefulness, mindful judgement constructs (taste and environmental concerns), trust and perceived safety. Concerns about the environment are addressed in the bottled water context because of its ubiquitous use and increasing sales. This increasing bottled water use raises the question about why people drink bottled water versus tap water and provides a venue for testing how mindfulness influences the decision process. This study contributes to the literature by providing a new application of technology acceptance model (TAM) that includes the 'mindful' judgement construct as well as the context of applying TAM to a non-traditional technology. This research found that increasing mindfulness of environmental concerns in our community limits bottled water consumption. The statistically significant findings of this research suggest that companies can benefit from examining their manufacturing and recycling processes.